A Systematic Review Of Randomized Controlled Trials Assessing The Effect Of L-Carnosine On Children With Attention Deficit Hyperactivity Disorder (Journal of Pharmaceutical Negative Results, 2023)
To evaluate the efficacy of L-Carnosine in children with Attention deficit hyperactivity disorder (ADHD) using existing data sources. Databases, such as PubMed, Scopus, Embase, and web of Science were searched using a comprehensive search strategy. Data were identified from randomized controlled trials (RCTs). The main outcomes were changes in inattention, hyperactivity or both based on ADHD rating scales by teachers, parents or both. Additional outcomes included improvement in sleep disorders, learning disabilities and adverse events. Jadad scale was used to assess the quality of RCTs. The risk of bias was assessed using modified Cochrane risk of bias tool. The protocol was registered with PROSPERO; registration number CRD42020209818. Two double-blinded, placebo-controlled RCTs with a total of 111 participants were selected for the review. Both the trials were methodologically of high quality as per the Jadad scale. There was a low risk of bias according to the modified Cochrane risk of bias tool. Both the studies showed no significant difference between L-Carnosine and placebo controls on majority of their outcome measures. The available data does not recommend the use of L-Carnosine in the management of children with ADHD owing to scarcity of studies. Further studies are needed to explore the effect of L-carnosine in management of ADHD.